Analise de uma agroindustria de tomate na Alta Sorocabana: as relacoes industria-produtor. - Grigoletto, M. F.; De, N. (My University, 1983)
Looks at the procedures used to organize producers and production in Alta Sorocabana, Brazil. An increasing subordination of the industry is leading to a loss in the competition for expansion. Spatial effects in the region and future trends in tomato cultivation are examined.-J.Robertson
Analysis of the tomato-growing industry in the Alta Sorocabana: relationships in the producing industry, Brazil